The Conflict Between Social Classes in Qur'anic and Marxist Expression: An Expressive and Interpretive Research - Makmun, Muhammad; Marpuah, Siti (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
This article aims to present the expressions of the Qur'an and the thoughts of Karl Marx on the issue of social class conflict. In contexts where human differences can become sources of conflict and contention, often leading to mutual degradation and destruction, this study is crucial. This research employs the